Incidence, predictors, and indications of permanent pacemaker implantation following orthotopic heart transplantation: A single-center experience - Iriagbonse Rotimi Asemota, MD; Siddharth Das; Michelle Nsahlai; Edward Graviss; Duc T. Nguyen; Paul A. Schurmann; Rayan Yousefzai, MD (JHLT Open)
In the modern era of orthotopic heart transplantation (OHT) with bicaval anastomosis, there is a paucity of data on permanent pacemaker implantation (PPI) in this population. This is a retrospective study describing the incidence, indication, and predictors in patients who underwent PPI after OHT. Using the transplant database from our institution between January 2016 and December 2022, 370 patients who had de-novo OHT were identified. The incidence of PPI post-OHT was 8.1% (n = 30 patients). The average time from OHT to PPI was 30.5 days. The most common indication for PPI was sinus node dysfunction, accounting for 83% of cases. Regarding predictors for PPI, multivariate analysis identified donor age as an independent predictor (hazard ratio 1.05, 95% confidence interval 1.01-1.09, p = 0.02). However, factors, including recipient age, ischemic time, sex, underlying cardiomyopathy, body mass index, mechanical support, pretransplant length of stay, and post-OHT length of stay, did not show significant predictive value.